The liver-enriched lnc-LFAR1 promotes liver fibrosis by activating TGFβ and Notch pathways - Kun Zhang (Nature Portfolio, 2017)
Activated hepatic stellate cells are the principal contributors to liver fibrosis by secreting a variety of pro-fibrogenic cytokines . Here Zhang et al. demonstrate that a liver-enriched lncRNA, lnc-LFAR1, promotes liver fibrosis and HSC activation by activating TGFβ and Notch signaling.